Use of Unmanned Aerial Vehicle Technologies with Thermal Imaging to Assess Surface Moisture in Pens of Cattle Offered Energy-dense vs. Low-energy Feeding Programs - Logan Diller (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: Characterize surface moisture levels in cattle pens as determined by different feeding programs and evaluate associations between unmanned aerial vehicle (UAV) thermal images and surface moisture in pens. Study Description: Six dirt-floor pens (30 × 50 ft) housing 14 dairy-beef crossbred steers each were assigned to an energy-dense, limit-fed ration (LIMIT; 64 net energy for gain [NEg]) or a low-energy ad libitum ration (ADLIB; 50 NEg). Each pen was divided into 15 quadrants, and pen floor samples were collected for moisture analysis. A UAV was flown to capture thermal images, which were processed to extract quadrant-level luminosity values. Associations between UAV-derived luminosity and direct moisture measurements were analyzed. The Bottom Line: Results confirmed low-energy, ad libitum pens were wetter than energy-dense, limit-fed pens, and luminosity values strongly predicted moisture with excellent agreement (CCC = 0.98).
Keywords: pen condition; UAV; thermal imaging